STRATEGIES FOR MEMORIZING THE QUR'AN FOR DEAF CHILDREN AT THE ABATA ISLAMIC BOARDING SCHOOL IN TEMANGGUNG - Muhamad Firzal Ihsan Syafiq; Fitriah M. Suud (LP2M IAI Al-Khairat Pamekasan, 2026)
This study aims to analyze the Qur'an learning strategy in improving the ability to read and memorize the Qur'an in deaf students. The hearing limitations possessed by deaf students require an adaptive and communicative learning approach so that the learning process can take place effectively. This research uses a qualitative approach with a case study type of research. Data collection techniques are carried out through observation, interviews, and documentation, while data analysis is carried out through data reduction, data presentation, and conclusion drawn. The results of the study showed that the learning strategies applied included the use of sign language, the use of lip movements and visualization, individual assistance (talaqi), memorization repetition (murojaah/tikrar), and the provision of motivation and rewards. This strategy has been proven to help deaf students in understanding the pronunciation of hijaiyah letters, improving reading articulation, and improving the ability to read and memorize the Qur'an. Thus, the application of adaptive, visual, and individual-mentoring-based learning strategies is an important factor in supporting the success of learning the Qur'an for deaf students.